Politics, Policy, and Inequality in South Africa Under COVID-19. (December 2020) - Francis, David; Valodia, Imraan; Webster, Edward
The COVID-19 pandemic has highlighted and exacerbated inequalities in South Africa. The question posed in this article is whether the pandemic and its associated responses offer the opportunity for a more egalitarian society in South Africa, or a more intensively unequal society. The future is contested. On the one hand, there is the consolidation of labor displacement, a growth in unemployment, and a deepening of inequality. On the other, there is the possibility of a turning point toward significant advances in the de-commodification of education, health, and transport. But as with much of the Global South, South Africa has relatively high levels of informality compared to the Global North, which has implications for the impact of the pandemic and the structure of the responses.